Wilson Disease: Update on Pathophysiology and Treatment - Dev, Som; Kruse, Robert L.; Hamilton, James P.; Lutsenko, Svetlana (Frontiers in Cell and Developmental Biology, 2022)
Wilson disease (WD) is a potentially fatal genetic disorder with a broad spectrum of phenotypic presentations. Inactivation of the copper (Cu) transporter ATP7B and Cu overload in tissues, especially in the liver, are established causes of WD. However, neither specific ATP7B mutations nor hepatic Cu levels, alone, explain the diverse clinical presentations of WD. Recently, the new molecular details of WD progression and metabolic signatures of WD phenotypes began to emerge. Studies in WD patients and animal models revealed the contributions of non-parenchymal liver cells and extrahepatic tissues to the liver phenotype, and pointed to dysregulation of nuclear receptors (NR), epigenetic modifications, and mitochondria dysfunction as important hallmarks of WD pathogenesis. This review summarizes recent advances in the characterization of WD pathophysiology and discusses emerging targets for improving WD diagnosis and treatment.